2009
DOI: 10.1002/dmrr.959
|View full text |Cite
|
Sign up to set email alerts
|

Taurine supplementation enhances nutrient‐induced insulin secretion in pancreatic mice islets

Abstract: TAU supplementation improves glucose tolerance and insulin sensitivity in mice, as well as insulin secretion from isolated islets. The latter effect seems to be, at least in part, dependent on a better Ca(2+) handling by the islets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
7

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 62 publications
3
29
0
7
Order By: Relevance
“…2B). This effect of taurine treatment is in agreement with some rodent studies that showed taurine administration attenuated the increase of blood glucose concentration during glucose tolerance testing [11][12][13][14][15][16][17] . In general, most glucose (>80%) is taken up by skeletal muscle 21) .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…2B). This effect of taurine treatment is in agreement with some rodent studies that showed taurine administration attenuated the increase of blood glucose concentration during glucose tolerance testing [11][12][13][14][15][16][17] . In general, most glucose (>80%) is taken up by skeletal muscle 21) .…”
Section: Discussionsupporting
confidence: 90%
“…Glycogen repletion in skeletal muscle after exercise is one of the major determinants of performance during subsequent exercise since higher pre-exercise glycogen content in skeletal muscle resulted in improving performance during both prolonged endurance and high-intensity intermittent exercise [2][3][4][5] . Some rodent studies have shown the possibility that taurine administration enhances glucose uptake in tissues [11][12][13][14][15][16][17] , which is one of the limiting factors for glycogen synthesis in skeletal muscle. Therefore, we hypothesized that taurine administration enhanced postexercise glycogen repletion in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that taurine concentrations are low in diabetic and pre-diabetic states and that physiological plasma taurine levels are important for adequate β-cell function and insulin action [135] . In MLP rat offspring, β-cell mass is decreased at birth and metabolic perturbations last through adulthood even though a normal diet is given after birth or after weaning [136] .…”
Section: Critical Windows Of Development and Avenues For Interventionmentioning
confidence: 99%